2008
DOI: 10.1103/physrevb.78.205301
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear spin dynamics and Zeno effect in quantum dots and defect centers

Abstract: We analyze nuclear spin dynamics in quantum dots and defect centers with a bound electron under electron-mediated coupling between nuclear spins due to the hyperfine interaction ("J-coupling" in NMR). Our analysis shows that the Overhauser field generated by the nuclei at the position of the electron has short-time dynamics quadratic in time for an initial nuclear spin state without transverse coherence. The quadratic short-time behavior allows for an extension of the Overhauser field lifetime through a sequen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 80 publications
3
51
2
Order By: Relevance
“…This is exactly the part of the Hamiltonian that is eliminated in most of the approaches by applying a strong magnetic field to the central spin system (see Refs. [31][32][33][34][35][36]. In Refs.…”
Section: A the Long Spin Approximationmentioning
confidence: 99%
See 1 more Smart Citation
“…This is exactly the part of the Hamiltonian that is eliminated in most of the approaches by applying a strong magnetic field to the central spin system (see Refs. [31][32][33][34][35][36]. In Refs.…”
Section: A the Long Spin Approximationmentioning
confidence: 99%
“…29 Following the idea to take advantage of the hyperfine interaction, in a recent paper 30 we investigated a system of two exchange-coupled electron spins, each of which is interacting with an individual bath of nuclear spins via the hyperfine interaction. In contrast to most of the approaches considered in the context of hyperfine interaction, [31][32][33][34][35][36] no magnetic field, enabling for a perturbative treatment of the problem, was applied to the electron spins. Using exact diagonalization studies, we demonstrated that the nuclear baths can be swapped and fully entangled, provided they are large enough.…”
Section: Introductionmentioning
confidence: 99%
“…However, a controllable nuclear spin polarization, acting as an effective magnetic field, can also become a resource for manipulating electron spins [21,22]. In particular, the difference (gradient) in the nuclear polarization of the left and right dots can be used for σ x rotations of a S-T 0 singlet-triplet qubit on the Bloch sphere [8].…”
Section: Introductionmentioning
confidence: 99%
“…For the case of a static exchange interaction J(t) = J 0 , the decay of the two-electron spin states in the S z = 0 subspace due to the Gaussian distribution of nuclear spin states may be calculated in several interesting limits [24,35]. Assuming the initial state of the two-electron system is ρ e (0) = |+ +|, the probability P + to measure the |+ state as a function of time is given by…”
Section: Hyperfine Interaction In Single and Double Dotsmentioning
confidence: 99%
“…Under these conditions the relevant spin Hamiltonian becomes block diagonal with blocks labeled by the total electron spin projection along the magnetic field S z . In the subspace of S z = 0 the Hamiltonian can be written as (h = 1) [24,35] …”
Section: Hyperfine Interaction In Single and Double Dotsmentioning
confidence: 99%